SOME FEATURES OF ARTERIAL HYPERTENSION, TAKING PLACE ON THE BACKGROUND OF OBESITY IN MEN OF WORKING AGE, EMPLOYEES IN THE SYSTEM OF INTERNAL AFFAIRS - A. O. Kovaleva (SINAPS LLC, 2017)
Aim. The aim of the study was to reveal the peculiarities of arterial hypertension, that occurs in male law enforcement officers of working age against the background of obesity, to evaluate the factors associated with obesity that affect hypertension. Materials and methods. The study included men of working age working in the system of internal affairs bodies and hospitalized on a scheduled basis in a cardiological hospital with the main diagnosis - arterial hypertension. All studied patients were divided into two groups, the first group included patients with arterial hypertension in combination with obesity, the second group included hypertension and normal body weight. All patients underwent a general clinical and indepth anthropometric examination. Instrumental examination of patients included echocardiography, 24-hour blood pressure monitoring and pulse oximetry. In addition, all patients had an assessment of the risk of obstructive sleep apnea syndrome and studied psycho-emotional status using standard questionnaires. Results and discussion. A comparative analysis of the two groups showed that significant differences were observed with respect to some anthropometric indicators. In patients with obesity, more pronounced signs of myocardial remodeling were revealed by the results of echocardiography. Also, patients of this group were more likely to develop obstructive sleep apnea syndrome, greater propensity to anxiety, combined with eating disorders, more often in a restrictive type. A comparative analysis of the diurnal blood pressure profile of the two groups showed no significant differences, but obese patients required significantly more intensive antihypertensive therapy to achieve target blood pressure figures. Conclusion. Obesity leads to more pronounced myocardial remodeling in working age men with arterial hypertension. More intensive antihypertensive therapy is required for compensation arterial hypertension in the case of obesity. Patients with obesity tend to develop a syndrome of obstructive sleep apnea and are characterized by a high level of anxiety and eating disorders.